2011
DOI: 10.1051/0004-6361/201117004
|View full text |Cite
|
Sign up to set email alerts
|

Studying the spatially resolved Schmidt-Kennicutt law in interacting galaxies: the case of Arp 158

Abstract: Context. Recent studies have shown that star formation in mergers does not seem to follow the same Schmidt-Kennicutt relation as in spiral disks, presenting a higher star formation rate (SFR) for a given gas column density. Aims. In this paper we study why and how different models of star formation arise. To do so we examine the process of star formation in the interacting system Arp 158 and its tidal debris. Methods. We perform an analysis of the properties of specific regions of interest in Arp 158 using obs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 78 publications
8
38
0
Order By: Relevance
“…High-spatial resolution observations can help to disentangle the role of largescale dynamics in the small-scale spatially resolved SF laws both in normal galaxies and in extreme starbursts (e.g. Boquien et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…High-spatial resolution observations can help to disentangle the role of largescale dynamics in the small-scale spatially resolved SF laws both in normal galaxies and in extreme starbursts (e.g. Boquien et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the overlap region of the Antennae galaxies, Wei et al (2012) observe a bimodal distribution of molecular clouds, finding both a population of GMCs typical of nearby galaxies and a population of unusually large, massive, and efficiently star-forming clouds. Boquien et al (2011) also previously reported significantly different star formation efficiencies in different regions of the interacting galaxy Arp 158, and Papadopoulos et al (2012) argue in general that accurate modeling of the interstellar medium (ISM) of luminous infrared galaxies (LIRGs) requires consideration of both a central dense, efficiently star-forming phase and a more diffuse disk-like component where star formation proceeds at a more modest pace.…”
Section: Introductionmentioning
confidence: 95%
“…However, regions with recent star formation are also regions where the atomic and molecular gas have the highest surface density, which makes their relative importance uncertain. Studies have shown that the emission of the warm gas is more closely associated to star formation than the emission of the cold gas (Bendo et al 2010(Bendo et al , 2012aBoquien et al 2011). In nearby galaxies, the warm-to-cold dust mass ratio has been shown to vary from ∼100 to a few 1000 s (e.g.…”
Section: Ionised Gasmentioning
confidence: 99%